Association Of Family Knowledge, Attitude, And Practice In Early Complementary Feeding With Stunting In Children Aged 6 - 23 Months In The Puskesmas Juanda - Anisa Afriani; Jamil Anshory; Satriani Satriani (Journal of Applied Food and Nutrition, 2022)
Background: Complementary food for breast milk (MP-ASI) was food or drink containing nutrients that is given to infants or children aged 6-24 months to meet nutritional needs other than breast milk, introduce new forms of food, and can form the immune system of children's. This study aims to determine the relationship between the level of knowledge, attitudes, and family practices on early complementary feeding with the incidence of stunting in the Puskesmas Juanda.Methods: This study was an analytic observational study with a cross-sectional approach. As many as 31 respondents aged 6-23 months were determined by the purposive sampling technique. Knowledge, attitudes, and family practices were obtained through questionnaires and analyzed with the Spearman rank test.Results: There is no significant relationship between knowledge with a p-value of 0.981 0.05 and a correlation coefficient of 0.005. Family attitude with p-value 0.608 0.05 and the correlation coefficient - 0.096. Family practice with p-value 0.299 0.05 and correlation coefficient value - 0.193.Discussion: The conclusion in this study is that there is no significant relationship between knowledge, attitudes, and family practices in early complementary feeding with the incidence of stunting.